Factors associated with persistent pain in college athletes with a history of lateral ankle sprain - Koshino, Y.; Watanabe, K.; Akimoto, M.; Ishida, T.; Samukawa, M.; Kasahara, S.; Tohyama, H. (Physical Therapy in Sport, 2023)
Objectives To determine the factors associated with and prevalence of persistent pain in college athletes with chronic ankle instability (CAI) and with previous lateral ankle sprain (LAS) without CAI.